Children's social/emotional characteristics at entry to school: Implications for school nurses. (September 2013) - Nelson, Helen; Kendall, Garth; Shields, Linda
Children entering school need to build healthy peer relationships; school, however, is the central place for bullying. School nurses have a growing focus on providing care for students with social, emotional and behavioural problems. We examined the relational development of children at school entry in regard to aggression and empathy, showing that teacher-reported aggression decreased between Pre-primary and Year One, while empathy increased between Year One and Year Two classes. No gender difference was found in teacher-reported total, or covert aggression. Understanding how development of empathy can be supported in children at school entry is important, thereby supporting development of pro-social behaviour and decreasing bullying. School nurses must understand the importance of surrounding children with safety in relationships as they begin school.